Determining the Effects of Training Duration on the Behavioral Expression of Habitual Control in Humans: A Multilaboratory Investigation - Perez-Riveros, O (COLD SPRING HARBOR LAB PRESS, PUBLICATIONS DEPT, 2022)
It has been suggested that there are two distinct and parallel mechanisms for controlling instrumental behavior in mammals: goal-directed actions and habits. To gain an understanding of how these two systems interact to control behavior, it is essential to characterize the mechanisms by which the balance between these systems is influenced by experience. Studies in rodents have shown that the amount of training governs the relative expression of these two systems: Behavior is goal-directed following moderate training, but the more extensively an instrumental action is trained, the more it becomes habitual. It is less clear whether humans exhibit similar training effects on the expression of goal-directed and habitual behavior, as human studies have reported contradictory findings. To tackle these contradictory findings, we formed a consortium, where four laboratories undertook a preregistered experimental induction of habits by manipulating the amount of training. There was no statistical evidence for a main effect of the amount of training on the formation and expression of habits. However, exploratory analyses suggest a moderating effect of the affective component of stress on the impact of training over habit expression. Participants who were lower in affective stress appeared to be initially goal-directed, but became habitual with increased training, whereas participants who were high in affective stress were already habitual even after moderate training, thereby manifesting insensitivity to overtraining effects. Our findings highlight the importance of the role of moderating variables such as individual differences in stress and anxiety when studying the experimental induction of habits in humans.